Didactic provision of the development of competency of intercultural communication of students in teaching English. - Tajiboyeva Fotimaxon Voxidjon qizi (Genius Journals, 2025)
This article explores the didactic approaches to developing students' intercultural communication competency in English language teaching. The study highlights the importance of intercultural competence in a globalized world and suggests effective didactic strategies for fostering this skill in students. Various methodologies and instructional techniques are analyzed to determine their effectiveness in enhancing intercultural communication abilities. The research provides a framework for educators to implement intercultural communication strategies in the classroom effectively
Keywords: Intercultural communication; didactic provision; English language teaching